Theorizing space-time relations in education: the concept of chronotope - Ritella, Giuseppe; Ligorio, Maria Beatrice; Hakkarainen, Kai (Frontline Learning Research, 2017)
Due to ongoing cultural-historical transformations, the space-time of learning is radically changing, and theoretical conceptualizations are needed to investigate how such evolving space-time frames can function as a ground for learning. In this article, we argue that the concept of chronotope – from Greek chronos and topos, meaning time and place/space – lends itself well to reach this aim. In particular, we outline three features of chronotope: 1) its analytical focus includes the examination of the potential interdependency between space and time; 2) it allows us to examine space and time as social constructions, negotiated in dialogical interaction; 3) it involves the analysis of both the material organization and the discursive negotiation of space and time. We use examples from our own studies and from relevant literature to illustrate how these features of the concept allow us to examine the role that space-time relations play in educational practice. Finally, we draw our conclusions and briefly introduce the theoretical and methodological challenges to be addressed for a full development of the concept.